PEMBUATAN STARTER UNTUK EKSTRAKSI MINYAK KELAPA MURNI MENGGUNAKAN MIKROBA AMILOLITIK - Naiola, Elidar (Research Center for Biology-Indonesian Institute of Sciences, 2008)
The thirteen isolates of amylolitic microbes had been tested their ability to extract the oil from